Market Design for a Gas Shortage - Axel Ockenfels (Wirtschaftsdienst)
Abstract So far, it is unclear who will get how much gas at what price in a gas shortage situation in Germany when the regulator has to ration. This threatens to dilute incentives in and in advance of a shortage. This paper looks at the potentially helpful role of a market for gas usage certificates for allocation and pricing in a shortage situation.